Phytochemical composition and chemical profiling of extracts of Cordia grandicalyx Oberm - Mildred A. Chauke; Motetelo A. Mogale; Ladislaus K. Mdee; Leshweni J. Shai (AOSIS, 2022)
Background: The search for bioactive organic products for the treatment of various diseases is a growing concern worldwide, because these bioactive natural products are associated with fewer side effects and are easily accessible. Aim: The present study analysed the phytochemical constituents and cytotoxic effects of the leaf, bark and fruit extracts of Cordia grandicalyx Oberm. Setting: Plant samples were collected from Ga-Mashishimale village in Ba-Phalaborwa Municipality, South Africa. Methods: Antioxidant activity was determined through 1,1-diphenyl-2-picrylhydrazyl radical scavenging method, whilst cytotoxic assay was assessed using the 3-[4,5-dimethylthiazol-2-yl]-2,5 diphenyl tetrazolium bromide method. Plant extracts were subjected to phytochemical profiling using both qualitative and quantitative methods. The extracts were also subjected to fractionation using column chromatography and thin-layer chromatography, and the sub-fractions with considerable yields were identified using nuclear magnetic resonance (NMR). Results: The aqueous extracts of the bark and leaves had significant (p 0.001) antioxidant activity as compared to negative controls and ascorbic acid. Additionally, appreciable amounts of total phenolic and alkaloid contents were recorded on polar extracts, notably 200 mg/GAE and 140 mg/quercetin equivalents for leaf cold water and leaf hot water extracts, respectively. All extracts were not toxic to cells, whilst the positive control (H2O2) led to almost 100% demise of cells. Two compounds were isolated from the leaf acetone extracts collected from fraction 20 to 30 and fraction 101 to 120 and identified as α˗amyrin and β-amyrin by NMR spectral analysis. Conclusion: The study provided evidence supporting the screening of plants for the discovery of therapeutic compounds. The study also revealed that all the different C. grandicalyx extracts were less toxic to cells and may provide scientific backing for continued use of the plant in mixtures for the treatment of diseases.